Collection and genetic characterization of Vitis vinifera ’ Žilavka’ by microsatellites and AFLP markers - Lidija TOMIĆ; Nataša ŠTAJNER; Tatjana JOVANOVIĆ CVETKOVIĆ; Miljan CVETKOVIĆ; Branka JAVORNIK (Acta Agriculturae Slovenica)
‘Žilavka’ has been grown in Bosnia and Herzegovina since the XIVth century and is exploited for wine production. Although not sufficiently studied, this grapevine cultivar has high economic potential for the country. Five survey missions resulted in the collection of eighty ‘Žilavka’ accessions that varied in terms of names and characteristics. Because of the unknown origin of the cultivar, these accessions were analyzed with microsatellites markers in order to obtain a standard ‘Žilavka’ genotype. AFLP markers were used to investigate the genetic basis of variability within the cultivar. ‘Žilavka’ grapevines were screened on 14 microsatellite loci, thus revealing 4 different genotypes arising from mutations observed at 10 polymorphic loci. AFLP analysis of 52 ‘Žilavka’ accessions revealed 35 different genotypes, with an average polymorphism of 57 %. Cluster analysis showed no grouping of different Žilavka accessions according to their names, characteristics or collection locations. The standard ‘Žilavka’ genotype was further compared to 211 cultivars from Slovenia (49), Austria/Germany (20), France (13), Portugal (27), Croatia (19), Greece (32), Spain (21) and Italy (30) in order to assess their genetic relationships. In pairwise comparisons, the highest genetic similarity was found with Slovenian cultivars ‘Glera’ and ‘Briška Glera’ (64 %) and the highest genetic dissimilarity (100 %) with two Italian cultivars, ‘Nebbiolo Lampia’ and ‘Vespolina’. Inventory, collection and genetic characterization of ‘Žilavka’ accessions are important steps towards cultivar standardization, identification of parental cultivars and investigation of cultivar origin, required for its sustainable use.